A multi-functional iodoplumbate-based hybrid crystal: 1-propyl-4-aminopyridinium triiodoplumbate. Issue 37 (27th April 2017) - Duan, Hai-Bao; Yu, Shan-Shan; Liu, Shao-Xian; Zhang, Hui
Abstract : The temperature-dependent photoluminescence, dielectric and impedance spectra, as well as crystal structures have been investigated for the iodoplumbate-based hybrid crystal, [C3 -Apy][PbI3 ] (1 ) (C3 -Apy + = 1-propyl-4-aminopyridinium). Abstract : The temperature-dependent photoluminescence, dielectric and impedance spectra, as well as crystal structures have been investigated for the iodoplumbate-based hybrid crystal, [C3 -Apy][PbI3 ] (1 ) (C3 -Apy + = 1-propyl-4-aminopyridinium). Compound1 in the room temperature (RT) contains [PbI3 ]∞ chains formed by face-sharing distorted PbI6 octahedral. In the low-temperature (LT) phase, the disordered propyl groups in HT phase are partly ordered.1 shows novel dielectric relaxation and thermochromic luminescent properties.